IMPLEMENTASI RFID TAG PASIF SEBAGAI PENGAMAN TAMBAHAN PADA SEPEDA MOTOR - Muhammad Riyan Alwin; Addy Suyatno; Indah Fitri Astuti (Mulawarman University, 2012)
RFID can be implemented in the security system on motorcycle and cars. Each vehicle already has security standards but with this addition of the security using RFID, the owners will more secure from loses. many cases of motor vehicle theft encourage the development of security systems which is used to reduce those thefts. The work of this device is utilizing the ignition engine or CDI (Capacitor Discharge Ignition) and Coil (raising the voltage to spark plug). Between the CDI and coil is installed a hardware device which is can terminate and connect the electricity, the device is using RFID sensors. RFID uses the radio frequency to read the information from a small device called a tag or transponder. RFID tag will recognize itself when a signa is detected l from a compatible device, that is the RFID reader. Appliance placed in a hidden place and also easily detected signal by the RFID tag. By adding this device, the motorcylce has now a double security system and reduce users concern because it can use the handlebar lock, it can also be secured with RFID system.